Total Diet Replacement Within an Integrated Intensive Lifestyle Intervention for Remission of Type 2 Diabetes: Lessons From DiRECT - Noronha, Jarvis C.; Thom, George; Lean, Michael E. J. (Frontiers in Endocrinology, 2022)
The prognosis for people with type 2 diabetes (T2D) remains concerning, yet its seriousness is often underestimated. T2D is a manifestation, in susceptible individuals, of the disease-process of obesity, and at diagnosis, 10-year survival rates for T2D are around 50%. Here, we will examine: (a) the role of weight loss in T2D, (b) use of total diet replacements (TDRs) to induce weight loss, (c) the Diabetes Remission Clinical Trial (DiRECT) protocol and key results, (d) other dietary interventions related to T2D remission, (e) remission in real life, and (f) future directions. Remission of short-duration T2D will usually require 10-15% body weight loss, and results from the DiRECT trial demonstrated that this can be achieved within routine care in nearly half of all people undertaking a supported, TDR-led behavioural weight management programme. In light of these findings, which have since been replicated in the Diabetes Intervention Accentuating Diet and Enhancing Metabolism (DIADEM-I) trial conducted in the Middle East and North Africa, it is now time to prioritize weight loss programmes for T2D remission from diagnosis, and with increasing acceptance and availability of digital healthcare, there is an opportunity to scale up delivery of remission programmes in a cost effective manner.